(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Social media has become an important source of travel information, particularly in tourism contexts where decisions depend on reviews, visual content, route information, accommodation details and previous travellers’ experiences. The objective of the study was to assess social media-based information behaviour influences tourists’ information satisfaction and post-trip sharing behaviour in Himachal Pradesh. Drawing on the Technology Acceptance Model and the Information Systems Success Model, the study develops an integrated framework linking pre-trip search behaviour, social media awareness, information usefulness, information satisfaction and post-trip sharing behaviour. Data of 600 tourists was analysed. Descriptive statistics, reliability analysis, correlation analysis, regression-based path analysis and bootstrapped mediation tests were used to examine the proposed relationships. The findings show that social media awareness significantly improves both information usefulness and information satisfaction. Post-trip sharing behaviour is significantly influenced by pre-trip search behaviour, social media awareness, information usefulness and information satisfaction. However, the proposed mediation effects are not supported, indicating that tourists’ social media behaviour is more direct than sequential. The study contributes to tourism literature by linking pre-trip information search with post-trip sharing within a single empirical framework and by highlighting the distinct roles of information usefulness and satisfaction in social media-based tourist behaviour. The findings suggest that destination managers should treat social media not merely as a promotional channel but as a practical information ecosystem that supports travel planning, tourist confidence and post-trip electronic word-of-mouth.